Necropolitics and Biopower in the Pandemic: Death, Social Control or Well-Being - Sagot Rodríguez, Montserrat (2022)
Every crisis creates its own ways to experience life, and, in some cases, death. The crisis generated by COVID-19 allows us to see the worst of times and the best of times to live and die, but it has also opened up the possibility to imagine better times. The crisis is transforming our ways of envisioning the world and how we live in the it. This is why this is not a health crisis, as some have called it. The COVID-19 pandemic has the potential to become a civilizational crisis that could disrupt social relations, the organization of production, the role of states, the path of neoliberal globalization and even the place of humans in history and nature. This chapter will explore these deeper aspects of the crisis of contemporary capitalism, especially how the pandemic made contemporary necropolitics and biopower even more visible.